2015
DOI: 10.1179/0027773815z.000000000110
|View full text |Cite
|
Sign up to set email alerts
|

Island Placenaming and Insular Toponymies

Abstract: Islands as distinct research sites have been given little specific attention by toponymists. The physical segregation, distinctness, and isolation of islands from continental environments may provide linguists and onomasticians with significant micro case studies for examining the role of toponyms as proper names. This article outlines the possibility of how the cultural and ecological nature of the toponymy of (small) island situations contributes to a place’s onomasticon. It is claimed the principal differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Furthermore, there is a tradition on Majorca of conserving, throughout centuries and generations, the indicative toponyms given to large rural properties (possessions), which generally come from the family names 8 of ancient owners. This bears a certain resemblance to the situation described by Nash (2015) on the island of Norfolk. Similarly, the names of actual houses survive their owners, and on the Pityusic Islands (Ibiza, Formentera, S'Espalmador, and other small surrounding islets), as a consequence of their disperse populations, it is particularly common to assign place names to houses based on the anthroponym 9 of its current or historical owner (Ordinas, 1994).…”
Section: Baleares: the Islands And Their Microcosmsmentioning
confidence: 66%
See 4 more Smart Citations
“…Furthermore, there is a tradition on Majorca of conserving, throughout centuries and generations, the indicative toponyms given to large rural properties (possessions), which generally come from the family names 8 of ancient owners. This bears a certain resemblance to the situation described by Nash (2015) on the island of Norfolk. Similarly, the names of actual houses survive their owners, and on the Pityusic Islands (Ibiza, Formentera, S'Espalmador, and other small surrounding islets), as a consequence of their disperse populations, it is particularly common to assign place names to houses based on the anthroponym 9 of its current or historical owner (Ordinas, 1994).…”
Section: Baleares: the Islands And Their Microcosmsmentioning
confidence: 66%
“…In line with McCall's (1994) fourth assertion, this mainly corresponds to Balearic hunting grounds, mushroom breeding grounds, ancient hiding places for contraband, and fishing grounds. A study of Majorcan thalassonyms (maritime toponymy) (Lucas & Ordinas, 2013) confirmed that the methods for locating and creating place-names is the same in Majorca as in other distant places (Forman, 1967;Nash, 2015). From a linguistic point of view, the Balearic Islands show clear toponymic differences with respect to non-island territories.…”
Section: Baleares: the Islands And Their Microcosmsmentioning
confidence: 91%
See 3 more Smart Citations